My Very First Word Book - "ANGELA WILKES"; Dorling Kindersley (Family Learning from Dorling Kindersley Ltd Orlando, Florida, USA., 1993)
A colorful picture word book designed to help young children build their vocabulary. The book introduces everyday objects and themes with clear labels and engaging illustrations, encouraging early language development and word recognition.
At home -- Clothes -- Food -- Toys -- Opposites -- Numbers -- Colors -- Shapes -- Wild animals -- Farm animals -- Vehicles -- In the garden -- At the seaside -- In the town.
"Includes colorful illustrations." "Published with sturdy, child-friendly pages." "Part of the 'My Very First' series of books."
Ages 2 to 5.
Text in English.
Hardcover
Keywords: Vocabulary -- Picture dictionaries, Juvenile literature